Technology as a threat to local values and culture among students: A case study in Sabah, Malaysia - Asmaa AlSaqqaf; Amina Ali; Hairuddin Yakup; Rosie Tanis; Hong Chuan; Fandi Ibrahim; Ke Hu (Academia Industry Networks, 2024)
The technological and cultural revolution, driven by media manipulation and intensified by social media's cross-border communication, threatens local values and culture (LVC) in any society. In Malaysia, emerging lifestyles significantly challenge LVC, especially among students. Limited research has examined how educators in Sabah perceive the impact of technology on student behaviours related to LVC, leaving a gap in understanding the region's cultural and educational challenges. This study explores educators’ perspectives regarding technological influences in Sabah. Utilising a qualitative case study, nine educators from different educational levels were interviewed individually to explore students’ behaviours in reflecting the LVC in Sabah, Malaysia, particularly in Kota Kinabalu and Tawau. The thematic analysis resulted in four themes, i.e., (a) personality development, (b) technological weakness, (c) emotional intelligence, and (d) suggestions to address student development and digital literacy. The study presented an argument with the previous findings concerning personality disorders in defending LVC due to technological influences. The study suggests the importance of defending LVC in shaping a civilised society. It also contributes new findings on the students' abilities to overcome the challenges of technological influences